POLA KOMUNIKASI KELUARGA PRASEJAHTERA DALAM PENGASUHAN PENDIDIKAN FORMAL DAN PEMAHAMAN NORMA SOSIAL ANAK - Azka Tsania Yahdini; Agus Naryoso; Muchamad Yuliyanto (Interaksi Online, 2022)
Communication between parents and children is important in the family as well as parenting. There is a need for stable economic conditions to support good communication and parenting. However, not all families have stable economic conditions. Many children from pre-prosperous families deviate because of the lack of formal education and understanding of social norms from their parents. However, not all children from pre-prosperous families are like that. Few of them manage to get an education and a good understanding of social norms. This study aims to understand the communication patterns of underprivileged families in formal education parenting patterns and understand children's social norms with qualitative research methods. This research refers to the interpretive paradigm with a phenomenological approach. The data collection technique used is an in-depth interview. The theories used in this research are Family Communication Pattern Theory, Non-Verbal and Verbal Communication Concepts, Relationship Maintenance Theory, and Differential Association Theory. The results of this study indicate that each family has a different pattern of communication. These are laissez-faire, consensual, and pluralistic types. In addition, to strengthen the relationship in the family, parents and children apply such as assurance, positivity, openness, sharing network, and sharing tasks. This study also found that informal education parenting and understanding social norms, parents apply different parenting patterns, including uninvolved, permissive, and authoritative. And based on this care, children can already understand well about formal education and understand social norms taught by their parents